Biodegradability of water treatment sludge influenced by sewage sludge, focusing its use in agriculture as soil conditioner - Franco, N. M. [UNESP]; Leite, D. A.N.O. [UNESP]; Yabuki, L. N.M. [UNESP]; Zanatta, M. B.T. [UNESP]; Menegario, A. A. [UNESP]; Angelis, D. F. [UNESP]; Mazzeo, D. E.C. [UNESP] (Springer Nature, 2021)
Water treatment plants are responsible for ensuring the quality and distribution of drinking water. The most commonly employed treatment method is the conventional type, which generates a significant amount of waste known as sludge. As chemicals are used throughout the treatment to remove impurities from the water, the sludge may contain toxic substances in its composition and, therefore, must receive an environmentally appropriate final disposition. This study aimed to assess, through respirometry, the biodegradability of water treatment sludge when applied to soil, associated or not with biostimulating material (sewage sludge), focusing on its use in agriculture. Before and after biodegradation, physical–chemical, microbiological, and phytotoxic potential characterization of the different treatments containing soil, water treatment sludge, and sewage sludge was also carried out. The chemical/biochemical oxygen demand ratio indicated the presence of less biodegradable compounds in the water treatment sludge compared to sewage sludge. The respirometry test revealed that the samples containing sewage sludge presented the highest CO2 production and biodegradation efficiency. The sample soil, sewage sludge, and 5% water treatment sludge showed the best result for these parameters. None of the treatments performed was considered phytotoxic, exhibiting germination percentages superior to 70%. The sample containing the highest concentration of water treatment sludge associated with sewage sludge presented a statistically significant increase in root growth after biodegradation. Thus, the addition of sewage sludge led to an increase in the agronomic potential of the mixture. Therefore, water treatment sludge as a soil conditioner seems to be a promising alternative for its recycling.
Keywords: Biodegradation; Phytotoxicity; Respirometry; Solid waste; Waste management